Early-TIPS Versus Current Standard Therapy for Acute Variceal Bleeding in Cirrhosis Patients: A Systemic Review With Meta-analysis - Li, Shuang; Zhang, Chao; Lin, Lu-Lu; Wang, Qi; Zuo, Hong-Xia; Zhan, Ai-Ling; Luo, Jie; Niu, Yu-Ming; Zhong, Guo-Qing (Frontiers in Pharmacology, 2020)
BACKGROUND: The survival of early placement (within 72h after admission) of transjugular intrahepatic portosystemic shunts (early-TIPS) in patients with cirrhosis and acute variceal bleeding (AVB) is controversial. OBJECTIVES: We performed a systemic review and meta-analysis to assess whether early-TIPS could improve survival in patients with cirrhosis and acute variceal bleeding. METHODS: Systematic search of the literature was conducted from PubMed, EMBASE, and Cochrane Library published before June 25, 2019 for eligible studies that compared early-TIPS with a combination of endoscopic variceal ligation (EVL) or endoscopic injection sclerotherapy (EIS) plus pharmacotherapy in the therapeutic effect in AVB patients. RESULTS: A total of 5 studies with 1,754 participants were enrolled. The early-TIPS demonstrated a significant improvement in prevention of treatment failure (OR=0.11,95%CI=0.05-0.23), 6-weeks mortality (OR=0.24,95%CI=0.13-0.46), rebleeding within 6 weeks (OR=0.21,95%CI=0.12-0.36), rebleeding within 1 year (OR=0.16,95%CI=0.07-0.36), new or worsening ascites (OR=0.33,95%CI=0.21-0.53), except in encephalopathy (OR=1.29,95%CI=0.996-1.67). For 1-year mortality, significant prior effect was also observed in early-TIPS (OR=0.64,95%CI=0.46-0.90), and the beneficial effect in Child-Pugh C patients (OR=0.35,95%CI=0.18-0.68) was equal to Child-Pugh B patients (OR=0.34,95%CI=0.25-0.58). No difference in liver transplantation and mortality caused by liver failure was observed. CONCLUSSIONS: Early covered-TIPS could be recommended for the management of AVB patients in cirrhosis with demonstrating a significant improvement in treatment failure, both short- and long-term mortality, rebleeding risk, and new or worsening ascites compared to standard therapy, especially for the high-risk AVB patients. It will also apply to patients in Child-Pugh A until the solutions to prevent hepatic encephalopathy in future researches were found.